2012
DOI: 10.1063/1.3672858
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fe composition on the superconducting properties (Tc, Hc2 and Hirr) of FexSe1/2Te1/2 (x = 0.95, 1.00, 1.05 and 1.10)

Abstract: In the present work, we have studied the effect of Fe composition on the superconducting properties, such as transition temperature (T c), upper critical field (H c2), and irreversibility field (H irr) of FeSe 1=2 Te 1=2. The polycrystalline samples have been prepared via solid state reaction route with nominal compositions Fe x Se 1=2 Te 1=2 (x ¼ 0.95, 1.00, 1.05 and 1.10). The x-ray diffraction results show the presence of tetragonal a-FeSe phase with the p4=nmm space group symmetry in all the samples. The z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
0
15
1
Order By: Relevance
“…The behavior above T * is unlikely to be related to the semiconducting hexagonal phase Fe 2 Te 3 because it is also seen in pure β-phase crystals, both in the literature [20] and in our crystals. It does not have a clear and unique interpretation but it may be related with the maximum in resistivity of β-FeSe at 350 K [26].…”
Section: Iiia Normal State Propertiesmentioning
confidence: 72%
See 1 more Smart Citation
“…The behavior above T * is unlikely to be related to the semiconducting hexagonal phase Fe 2 Te 3 because it is also seen in pure β-phase crystals, both in the literature [20] and in our crystals. It does not have a clear and unique interpretation but it may be related with the maximum in resistivity of β-FeSe at 350 K [26].…”
Section: Iiia Normal State Propertiesmentioning
confidence: 72%
“…The main features of the normal state resistivity in samples of the β-phase have been described in the literature [19,20,21,22]. A metallic like behavior was reported for the Se rich end.…”
Section: Iiia Normal State Propertiesmentioning
confidence: 95%
“…The mix of phases is possibly responsible for diverse behaviors reported in the literature for FeSe. Some authors observed that only samples near perfect stoichiometry display the highest transition temperatures [2]. Others that disorder and impurity phases enhance the superconducting properties [3].…”
Section: Introductionmentioning
confidence: 97%
“…Compared with Fe-based superconductors, [3][4][5][6][7][8][9][10][11] these non-toxic layered compounds with weak interlayer van der Waals forces exhibit interesting physical properties, including phase separation, 12 strong correlations, 13,14 non-trivial isovalent doping, [15][16][17] Fe excess effects, 18 Fe vacancy, [19][20][21] and rich high-pressure phase diagrams. 13,14,[22][23][24] Attention has also shifted to other non-Fe transition metal based chalcogenides as they are shedding light on the road to the post-iron age in superconductivity.…”
Section: Introductionmentioning
confidence: 99%